Public-private mix for DOTS implementation: what makes it work? - Knut Lönnroth; Mukund Uplekar; Vijay K. Arora; Sanjay Juvekar; Nguyen T.N. Lan; David Mwaniki; Vikram Pathania
OBJECTIVE: To compare processes and outcomes of four public-private mix (PPM) projects on DOTS implementation for tuberculosis (TB) control in New Delhi, India; Ho Chi Minh City, Viet Nam; Nairobi, Kenya; and Pune, India. METHODS: Cross-project analysis of secondary data from separate project evaluations was used. Differences among PPM project sites in impact on TB control (change in case detection, treatment outcomes and equity in access) were correlated with differences in chosen intervention strategies and structural conditions. FINDINGS: The analysis suggests that an effective intervention package should include the following provider-side components: (1) orienting private providers (PPs) and the staff of the national TB programme (NTP); (2) improving the referral and information system through simple practical tools; (3) the NTP adequately supervising and monitoring PPs; and (4) the NTP providing free anti-TB drugs to patients treated in the private sector. CONCLUSION: Getting such an intervention package to work requires that the NTP be strongly committed to supporting, supervising and evaluating PPM projects. Further, using a local nongovernmental organization or a medical association as an intermediary may facilitate collaboration. Investing time and effort to ensure that sufficient dialogue takes place among all stakeholders is important to help build trust and achieve a high level of agreement.